The Anthropocene: age of complexity, foresight and innovation?. Issue 5 (10th September 2018) - Richardson, Jacques G.; Erdelen, Walter Rudolf
Abstract : Purpose: Specific examples or brief case-histories in different fields or disciplines illustrate the inventive process from conception to realization. Design/methodology/approach: The authors examine predictions made in 2007 by "China experts" about what the Chinese business environment would look like in 2017. Their predictions were accurate in respect of around two-thirds of the issues they were asked to consider. The authors focus on the one-third of issues about which they were wide of the mark and examine the likely reasons. Findings: The newly named Anthropocene is a time of increasing conception, research, design, development, evaluation and exploitation of new artifacts and services. Objectivity: careful problem-analysis assures the authors' understanding of innovating pathways. Research limitations/implications: Trial-and-error methods may be disorderly, log-type research records are not kept, accidents not considered relevant. Originality/value: Examples cited are transdisciplinary, often requiring inputs from other economic or cultural sectors. These complexities should be of incalculable value to innovators with single-field backgrounds.